Hydrothermally grown ZnO micro/nanorods fabrication and growth mechanism - Putungan, Alexandra B. Santos; Sarmago, Roland V. (2015)
Highly crystalline ZnO micro/nano were fabricated via the hydrothermal synthesis method, a promising alternative fabrication technique for large scale production. It is found that the precursors' concentration does not influence the micro/nano rods' crystal structure parameters, while it affects the average physical dimensions proportionally. A growth mechanism model that is based on the dissociative nature of the method and polar nature of ZnO terminations is proposed in order to shed light on the unique branching pattern of the micro/nano rods as they grow in size. The results are of importance in the understanding of structures' growth in low-dimensional systems, and could pave the way for the further advancement of nanotechnology-based applications.
Keywords: Semiconductors; Nanotechnology